A need for values - Brunetti, Immacolata (Formazione & insegnamento, 2013)
Background: Professional commitment on behalf of teachers requires more than contractual compliance as personal and professional values appear intrinsic to teaching practice. Teachers are expected to act as role models and demonstrate positive attributes and attitudes in an evolving educational context. Little is known about how they understand and interpret their own values, or realise the shared values that lie at the heart of a school community. Purpose: The purpose of this review is to summarise the literature about the values held by teachers. The review is concerned with theoretical and empirical studies in which such values are considered, as well as studies in which tensions are identified between the personal values of teachers and the organizational values of the school—especially when they are reflected in professional practice. Design and methods: An extensive literature review was undertaken concerning the values held by school professionals. The investigation was conducted using the Electronic Journal Service, which is a database that covers a wide range of subjects; moreover, general search engines have been used (e.g. Google.it, .co.uk, .fr). Conclusion: This review highlights the integral part values continue to play in education. Studies in the context of values and professionalism stress the need for dialogue and reflection so that implicit values that teachers hold become explicit, and refined through practice.